4,7-Dihydroindole: A Synthon for the Preparations of 2-Substituted Indoles - Kilic, Haydar; Bayindir, Sinan; Saracoglu, Nurullah (Current Organic Synthesis, 2014)
This review covers the functionalization of 4,7-dihydroindole derivatives as synthetic equivalents (synthons) for 2-substituted indoles.
Keywords: Friedel-Crafts alkylation